Physiological Parameters Among Mountain Hikers - Jargaltulga Ulziijargal; Enkhgerel Nyamdavaa (Central Asian Journal of Medical Sciences)
Objectives: This study aims to investigate the impact of outdoor activities, particularly mountain hiking, on physiological parameters, focusing on comparing differences between office workers and professional climbers. By analyzing factors such as waist circumference and exercise frequency, the objective is to assess the potential health benefits associated with active lifestyles and inform strategies for promoting physical activity among sedentary populations. Methods: The survey was collected using a cross-sectional study method from 3 target groups, including professional mountaineers, amateur climbers, and office workers, in October 2022. The main questionnaire of the study included the WHO non-communicable disease risk questionnaire, the frequency and amount of mountain climbing, and the frequency and amount of active exercise. We also measured the physiological parameters of the participants. The statistical analysis was done using SPSS 26.0 software. Results: Engaging in unhealthy habits among office workers causes men to have a higher waist circumference than their standard size, and most do not exercise regularly. In contrast, professional climbers' risk factors for non-communicable diseases were relatively low. Office workers who are inactive and work in conditions that require some physical activity have the greatest need for exercise but are not actively exercising. Conclusion: Outside of work, an individual makes time to climb a mountain, which can positively affect physiological parameters.